Skin diseases associated with the cosmetics use - Szybiak, Jagoda; Wiechuła, Danuta (Dermatology Review/Przegląd Dermatologiczny, 2013)
Rapid growth of cosmetics industry, the development of new technologies and the fashion for beautiful and young skin caused that cosmetics became essentials for modern society. Cosmetics, beeing everyday products by definition should act as protective, nursing and beautifying, and – most importatntly – should be safe and harmless for humans. Favorable effects of cosmetics on the skin are widely known and valued, whereas less is said about the adverse reactions frequently induced by them. Most common adverse re action to cosmetics include: contact dermatitis, contact urticaria, photosensitizing reactions, cosmetics acne and pigmentation disorders. In the paper clinical symptoms and pathogenesis of this reactions as well as factors predisposing to their development are discussed. The examples of cosmetics ingredients which usually cause these type of reactions are also presented.